2008
DOI: 10.1213/ane.0b013e3181685014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Phantom Limb Pain: The Effects of Calcitonin, Ketamine, and Their Combination on Pain and Sensory Thresholds

Abstract: Our results question the usefulness of calcitonin in chronic phantom limb pain and stress the potential interest of N-methyl-D-aspartate antagonists. Sensory assessments indicated that peripheral mechanisms are unlikely important determinants of phantom limb pain. Ketamine, but not calcitonin, affects central sensitization processes that are probably involved in the pathophysiology of phantom limb pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 31 publications
2
121
0
Order By: Relevance
“…Ketamine has been used clinically as an acute anesthetic for Ͼ40 years, and it also has analgesic effects on chronic pain including neuropathic pain in humans and animals (Parsons et al, 1993;Eichenberger et al, 2008). Racemic ketamine contains the optical isomers, S-and R-ketamine, which show stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine has been used clinically as an acute anesthetic for Ͼ40 years, and it also has analgesic effects on chronic pain including neuropathic pain in humans and animals (Parsons et al, 1993;Eichenberger et al, 2008). Racemic ketamine contains the optical isomers, S-and R-ketamine, which show stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study, in contrast to clinical experience, showed a rapid analgesic onset (approximately 80 minutes) and a short duration (up to 180 minutes). The effect of CT (IV 200 IE) in patients with chronic phantom pain did not show any modulation of pain thresholds to electrical (temporal summation), thermal, and pressure stimulation, 32 indicating that the pain parameters evaluated may not represent the possible pain mechanisms affected by CT. Experimental pain models, such as pressure algometry, have been used in clinical studies.…”
Section: Clinical Settingmentioning
confidence: 93%
“…There is one human experimental clinical study on chronic phantom limb pain 32 where CT, CT and ketamine in combination, or ketamine alone was given. Together with the clinical pain parameters some experimental pain …”
Section: Compounds Interacting With the Analgesic Effect Of Calcitoninmentioning
confidence: 99%
“…There was also significant improvement 24 h post-infusion of the effect of pain on their general activity and enjoyment of life over the placebo group. Ketamine administered intravenously in doses ranging from 7 mcg/kg/min to 0.4 mg/kg for 45-60 min also showed efficacy in decreasing residual limb and phantom pain in two randomized, double-blind crossover studies [83,84].…”
Section: Literature On Ketamine Use In Ischemic Limb Pain and Phantommentioning
confidence: 97%